2019
DOI: 10.3389/fimmu.2019.02634
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Maintenance of Foxp3+ Treg Cells in Non-lymphoid Microenvironments

Abstract: Foxp3+ Treg cells are indispensable for maintaining self-tolerance in secondary lymphoid organs (SLOs). However, Treg cells are also recruited to non-lymphoid tissues (NLTs) during inflammation. Recent advances in the understanding of Treg cell biology provided us with molecular mechanisms—both transcriptional and epigenetic—that enable Treg cells to retain their identity in an inflammatory milieu that is per se hostile to sustained expression of high levels of Foxp3. While Treg cells are recruited to sites of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 70 publications
1
34
0
Order By: Relevance
“…Another subset of T cells, termed regulatory T cells (Treg), are also recruited to sites of inflammation in peripheral tissues in order to resolve inflammation and restore the correct organ function 64 . Recently, Dong et al suggested some natural regulation of ovarian integrity by Tregs, since depletion of Treg cells by neonatal thymectomy results in autoimmune ovarian disease 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Another subset of T cells, termed regulatory T cells (Treg), are also recruited to sites of inflammation in peripheral tissues in order to resolve inflammation and restore the correct organ function 64 . Recently, Dong et al suggested some natural regulation of ovarian integrity by Tregs, since depletion of Treg cells by neonatal thymectomy results in autoimmune ovarian disease 65 .…”
Section: Discussionmentioning
confidence: 99%
“…The previous research proved that Tregs could promote progression of ESCC, whereas both Tregs and fibroblasts were relevant to unfavorable survival in patients with ESCC (Fu et al, 2011;Nabeki et al, 2015;Yue et al, 2020). Meanwhile, α-SMA and Foxp3 are specific biomarkers of fibroblasts and Treg cells (Korn and Muschaweckh, 2019;Zhan et al, 2019). To confirm our analytical results, we first selected two representative tumor samples from the high-and low-risk groups and stained α-SMA and Foxp3 in the two tumor sample slices using the immunofluorescent assay method.…”
Section: Relationship Between the Risk Score And Immune Landscapesmentioning
confidence: 98%
“… 105 In addition, it has been established that other proinflammatory cytokines or lipopolysaccharide promote Foxp3 degradation. 106 Likewise, several signaling pathways such as these involving the TF NFκB (nuclear factor κ-light-chain-enhancer), IRF (interferon regulatory factor)-4, Runx (Runt-related transcription factor), FoxP (Forkhead box protein P)-1, the nuclear protein DBC (deleted in breast cancer)-1, and serine/threonine-Pak (protein kinase)-2 (reviewed in study by Korn and Muschaweckh 107 ) as well as self-peptide induced TCR-signaling 108 have been linked to the plasticity of T regs . Altogether, these findings demonstrate a strong association of inflammation and T reg -instability, which sparks the yet unproven hypothesis that the multitude of factors that initiate and maintain atherosclerosis, such as local and systemic inflammation, LDL (low-density lipoprotein), vascular integrity and injury, immune cell accumulation, and antigen-recognition by T regs , favor a stage- and context-specific conversion of an initial protective into a pathogenic immune response (Figure 2 ).…”
Section: The Cxcr6 + Multilineage Committed T-helpmentioning
confidence: 99%